The Boulez-Cage Correspondence - Nattiez, Jean-Jacques 1945-; Samuels, Robert -1962 (Cambridge University Cambridge New York, 1993)
Between May 1949 and August 1954 the composers Pierre Boulez and John Cage exchanged a series of remarkable letters that reflect on their own music and the culture of the time. This correspondence, together with other relevant documents, has been edited and annotated by Jean-Jacques Nattiez and is now available for the first time in English in a paperback edition.This small but heavily annotated correspondence between French composer Pierre Boulez and recently deceased American composer John Cage contains letters dating from 1949 to 1954, as well as supplementary documents. The age difference between the two men is apparent, and the older Cage often assumes the role of teacher and mentor. The letters contain no striking personal revelations, but they record the activities and musical ideas of the composers, who at the time were moving in different directions. Often technical, the letters contain graphs and tables of sounds, durations, amplitudes, and more. The friendship between the composers later cooled, but these documents provide a historical record of the musical climate during the era of their relationship. Recommended for academic libraries.-- Debora Richey, California State Univ.
Keywords: Cage, John -- 1912-1992; Boulez, Pierre -- 1925-2016; Correspondence